TACROLIMUS INDUCED TREMORS AMONG POST RENAL TRANSPLANT PATIENTS: A CASE SERIES - Amita d; O, Balaji; Patil, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Triple immunosuppression in renal transplant has drastically changed the outcome of graft survival. However, concern always remains among the physicians because of adverse effects produced due to triple immunosuppression. Calcineurin inhibitors are associated with wide range of side effects. Hence, we report a case series of tremors associated with tacrolimus among renal transplant patients in a tertiary care hospital in southern India. Â